Immunosuppressive effects of MERTK in macrophages and cancer cells - Heiskanen, Nelli (My University, 2023)
Tumor-associated macrophages are an important factor regulating the tumor microenvironment due to their capability of removing apoptotic cancer cells. Tumor-associated macrophages are typically classified as anti-inflammatory M2 macrophages or pro-inflammatory M1 macrophages. TAM receptors (MERTK, AXL, and TYRO3), are an immunosuppressive receptor tyrosine kinase subfamily expressed in cells of the innate immunity, as well as in a variety of cancers, such as melanoma. In macrophages, MERTK can contribute to immunologically silent phagocytosis of cancer cells. In cancer cells, MERTK can promote cancer cell growth. In addition, MERTK may signal via its soluble intracellular domain released in proteolytic cleavage. In this thesis work, the role of MERTK in the immunosuppressive crosstalk of macrophages and cancer cells was investigated. Specifically, cancer cell-conditioned medium from cancer cells expressing different levels of MERTK was applied to THP-1 macrophages with endogenous or knocked down expression of MERTK. In addition, functionality of cleavage site-mutant MERTK constructs was tested in cells. The study showed that MERTK expression in cancer cells is associated with their ability to induce M2 polarization and that MERTK knockdown in macrophages inhibits their M2 polarization. Interestingly, cancer cell-conditioned medium from cell lines that express MERTK increased the expression of the MERTK ligand Gas6 in macrophages and MERTK knockdown in macrophages abrogated the effect. These results suggest that the autocrine Gas6 expression in macrophages is regulated by MERTK in at least macrophages, and possibly affected by MERTK expression in cancer cells. The analyses of the role of MERTK intracellular domain need further experimentation.
Keywords: MERTK, receptor tyrosine kinase, anti-tumor immunity, macrophage polarization